Hazardous chemicals : safety management and global regulations - Dikshith, T. S. S., 1932- (CRC Press, Taylor & Francis Group, 2013)
"Discusses various aspects of potentially toxic and hazardous chemicals in simple comprehensive language. Provides toxicity and health effects of chemicals in simple, nontechnical language. Covers scientific information on hazardous and potentially dangerous chemical substances at workplaces. Offers fundamental knowledge about the biological and health effects of hazardous and potentially toxic chemicals in a comprehensive way. Includes recent developments on safety management and potentially toxic chemicals and related global regulations."--Back cover